Meningkatkan Hasil Belajar Siswa Pada Materi SPLDV dengan Model Pembelajaran TAI Di SMP 18 Ma’arif Ibrohimi Jember - Brigita Carolina Dwi Kumala; Tri Susilaningtyas; Sholahudin Alayubi (FKIP Universitas Islam Jember, 2017)
This study aims to improve students' understanding of the SPLDV material by applying the Team Assisted Individualization (TAI) learning model. The type of research used is Classroom Action Research with the spiral system with the Hopkins model, which begins with preliminary action then continues with planning, action, observation, and reflection. The study was conducted in 2 cycles. Based on the results of the study, it was obtained that students' learning outcomes in cycle I obtained an average of 76,25 with a percentage of 65% and an increase in learning cycle II was obtained by an average of 88 with a percentage of 90%. This proves that the application of the TAI learning model can improve student learning outcomes on SPLDV material in class VIII SMP 18 Ma'arif Ibrohimi Karang Semanding. Keyword: Assisted Individualization (TAI), learning outcome.